Supporting Evidence-Informed Practice in Human Service Organizations: An Exploratory Study of Link Officers. Issue 1 (1st January 2017) - Graaf, Genevieve; McBeath, Bowen; Lwin, Kristen; Holmes, Dez; Austin, Michael J.
ABSTRACT: Human service organizations seeking to infuse research and other forms of evidence into their programs often need to expand their knowledge sharing systems in order to build their absorptive capacities for new information. To promote their engagement in evidence-informed practice, human service organizations can benefit from connections with intermediary organizations that assist with the dissemination and utilization of research and the use of internal knowledge brokers, called link officers . These boundary-spanning individuals work to embed external research and internal evidence in order to address current organizational priorities and service demands. This exploratory study describes the characteristics, major activities, and perceptions of link officers connected with three pioneering intermediary organizations. Quantitative and qualitative data from a survey of 137 Canadian and UK link officers provide a profile of these professionals, including how they engage practitioners to promote evidence-informed practice and the degree to which they are supported within their organizations and by intermediary organizations. The article concludes with practice and research implications for the development of the link officer role in human service organizations.